2021
DOI: 10.1080/2162402x.2021.1923910
|View full text |Cite
|
Sign up to set email alerts
|

Cldn-7 deficiency promotes experimental colitis and associated carcinogenesis by regulating intestinal epithelial integrity

Abstract: Intestinal epithelial barrier protects intestine from infection and injury, while chronic inflammation is a trigger for tumorigenesis. As a member of tight junctions (TJs) family, Claudin-7 (Cldn-7) is dedicated to maintaining cell polarity and TJs barrier integrity, and closely related to the development of inflammation and tumors. However, potential roles of Cldn-7 in intestinal inflammation and colitis-associated colorectal cancer (CAC) have not been well characterized in vivo. Here, we analyzed the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 47 publications
4
14
0
Order By: Relevance
“…S6G-I), indicating a role for cldn7b in regulating leukocyte infiltration in response to injury. These observations are consistent with those in Cldn7 knockout mice where loss of Cldn7 promoted leukocyte infiltration and intestinal inflammation by damaging the intestinal epithelium (Wang et al ., 2021), increasing intestinal epithelial permeability, and disrupting cell-matrix interactions (Ding et al ., 2012, 2022; Tanaka et al ., 2015). The structure of the RPE layer appeared overtly normal in unablated cldn7b knockout larvae (Fig, S6), and therefore the increased accumulation of macrophages/microglia in the RPE layer after injury might be related to the non-TJ function of claudin-7 in modulating cell-matrix adhesion.…”
Section: Resultssupporting
confidence: 91%
“…S6G-I), indicating a role for cldn7b in regulating leukocyte infiltration in response to injury. These observations are consistent with those in Cldn7 knockout mice where loss of Cldn7 promoted leukocyte infiltration and intestinal inflammation by damaging the intestinal epithelium (Wang et al ., 2021), increasing intestinal epithelial permeability, and disrupting cell-matrix interactions (Ding et al ., 2012, 2022; Tanaka et al ., 2015). The structure of the RPE layer appeared overtly normal in unablated cldn7b knockout larvae (Fig, S6), and therefore the increased accumulation of macrophages/microglia in the RPE layer after injury might be related to the non-TJ function of claudin-7 in modulating cell-matrix adhesion.…”
Section: Resultssupporting
confidence: 91%
“…To our knowledge, this is the first study to investigate the correlation of Claudin-7 immunohistochemical expression with inflammatory infiltrate in CRCs in humans. Consistent with our findings, but in animal models, Wang et al reported that loss of Claudin-7 increases colonic infiltration of leukocytes during experimental colitis and demonstrated the promotion of colitis and associated CRC colitis in a Claudin-7 knockout mouse model [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Especially, intestinal barrier-related genes such as Tjp1, Ocln, Cldn7 and Cldn15, which is induced by allulose treatment, are molecules that maintain tighter tight junction and contribute to enhancing intestinal barrier function and suppressing inflammatory responses. Recently, the role of Cldn7 was mechanistically demonstrated by Cldn7 knockout mice; loss of Cldn7 promotes colitis and subsequent malignant transformation by disrupting tight junction integrity and increasing the inflammation [ 33 ]. Thus, it is suggested that allulose has an effect not only on the digestive and absorptive capacity of nutrients, but also on the suppression of inflammatory bowel disease (IBD).…”
Section: Discussionmentioning
confidence: 99%